Aquimarina acroporae sp. nov., isolated from seawater surrounding scleractinian coral Acropora digitifera. Issue 10 (11th October 2022) - Sun, Hao; Rao, Chunhao; Yang, Xiaozhou; Xie, Ziqiang; Chen, Bogui; Zheng, Huina; Liao, Baolin; Xiao, Baohua
Abstract : A Gram-stain-negative, aerobic, rod-shaped bacterium (D1M17 T ) was isolated from the seawater surrounding scleractinian coral Acropora digitifera in Daya Bay, Shenzhen, PR China. Strain D1M17 T grew with 0–10 % (w/v) NaCl (optimum, 3–4 %), at 15–37 °C (optimum, 28 °C) and at pH 4.5–8.5 (optimum, pH 7.0–7.5). Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain D1M17 T formed a lineage within the genus Aquimarina, family Flavobacteriaceae, and it was distinct from the most closely related species Aquimarina salinaria LMG 25375 T, Aquimarina gracilis JCM 17453 T and Aquimarina spongiae KCTC 22663 T with 16S rRNA gene sequence similarities of 97.2, 97.2 and 97.1 %, respectively. The major respiratory quinone was MK-6. The predominant fatty acids (more than 10 %) were iso-C15 : 0 (28.8 %), iso-C17 : 0 3-OH (21.5 %) and iso-C15 : 1 G (13.1 %). The DNA G+C content of D1M17 T was 34.4 mol%. The polar lipids in D1M17 T comprised one phospholipid and five unknown polar lipids. Phenotypic characteristics (physiological, biochemical and chemotaxonomic) also supported the taxonomic novelty of this isolate. Thus, strain D1M17 T is considered to represent a novel species within the genus Aquimarina, for which the name Aquimarina acroporae sp. nov. is proposed. The type strain is D1M17 T (=KCTC 92172 T = MCCC 1K07224 T ).